Estrutura e dinâmica de famílias com um filho com necessidades educacionais especiais - FREITAS, Hilda Rosa Moraes de (Universidade Federal do Pará, 2014)
In the Brazilian context, research on the special educational needs focuses on the study of the difficulties and possibilities for inclusion of these students in regular classes of instruction, emphasizing the processes of teaching and learning. Few studies, in Brazil, see the family as the object of analysis, while not questioning its importance in child development. Thus, based on the bioecological model and the structural systemic theory, admitting to the family as a field of development common to all members it is necessary to know how it is structured to meet the demands arising from the special needs of your child and the effects of this dynamic in the group. From this it was aimed to describe the structure and dynamics of families of children with special educational needs, in addition to: analyze the interactions and relationships established within each subsystem (family, parent, sibling) and between them, and identify the organization family, from the mechanisms of cohesion and hierarchy in accordance with the structural systemic model. As the search strategy used the study of multiple cases, two families of children with special educational needs, a deaf girl, of ten years, and a boy, of twelve years old, with learning difficulties. The tools and techniques applied were: Roadmap for Semi-Structured Interview, Inventory of Routine (IR), Systematic Observation, Diary of Field, Family System Test (FAST) and Genogram. The scores obtained in the FAST were consistent with the results of IR, demonstrating greater cohesion in parent-child dyad that the father-child dyad, the two families, and the flexibility of borders in general, the perception of family was of border rigid, in systems, family, parent and sibling, and that the distribution of hierarchy was perceived by the parental dyad, in the two families, as a sign of preference for the sibling subsystem, and domination, for the parent subsystem, which interfered in the structures relational perceived by members. In assessing the sibling subsystem, the lack of power, represented by parents and representation by the children of this variable resulted in differences of perception in the group. Therefore, this study has, through the identification of relations and perceptions of members of families, to understand its dynamics and influence of, in developmental trajectory of children and the group, from, the demands arising from the diagnosis and strategies peculiar to each family to address the special needs of their children. Realizes that the family, the school's main partner in education, must be seen as a relational system whose strategies are fundamental for the child to have stimulated their skills and, thus, overcome their difficulties.